Teachers' empathy: can it be predicted by self-efficacy?. Issue 7 (2nd October 2016) - Goroshit, Marina; Hen, Meriav
Abstract: Teachers' social-emotional competencies seem to play a significant role in promoting social-emotional learning in schools. Empathic teachers were found to possess a higher level of morality; to communicate more successfully with their students; to encourage them to forge empathic relationships; and to successfully motivate their students. Yet, there is a dearth of literature on how to develop such empathy in teachers. The present study, which is based on a large body of research, investigated the contribution of teachers' self-efficacy and emotional self-efficacy to teacher empathy. The sample comprised 543 teachers from the central region of Israel who completed self-report questionnaires. Findings indicated that both types of self-efficacy contribute to empathy in teachers, but the contribution of teacher self-efficacy is greater. These findings can benefit teacher educators, principals and others involved in teacher performance and well-being throughout the world. Findings may suggest that both efficacies are compelling variables that need to be addressed and enhanced in relation to teacher empathy. In addition, the findings strengthen the notion that social-emotional competence in teachers is strongly associated with teachers' self-beliefs regarding their teaching efficacy.